Nonlinear finite element analysis of steel frame - Nadia Ashikin , Zainal Bahri (2012)
Finite element analysis (FEA) has become common place in recent years, and is now the basis of a multibillion dollar per year industry. Numerical solutions to even very complicated stress problems can now be obtained routinely using FEA, and the method is so important. This study is about modeling of steel frame structure using Ansys 12.0 (APDL) and determines the maximum deflection when the load is applied to the model. Ansys is software based on the finite element analysis (FEA) widely used in the computer-aided engineering (CAB) field. There are six random inputs will be used in this study which is Young Modulus (EX), Poison Ratio, Density, Area, Uniform Distributed Load (UDL) and Fy Loads. The random output will be the graph of maximum deflection. This study is going to be basic guidelines on how to implement the civil engineering element using Ansys software. This paper considers the practical application of nonlinear models in the analysis of steel structures. The results of some analyses performed using the steel model of the general purpose finite element code Ansys are presented and discussed. The differences observed in the response of the same steel frame as some variations are made in a material model that is always basically the same are emphasized. The consequences of small changes in modeling are discussed and it is shown that satisfactory results may be obtained from relatively simple and limited models.